2017
DOI: 10.7860/jcdr/2017/25367.9597
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nutritional Deficiency Anaemia and Its Impact on Scholastic Performance among Undergraduate Medical Students

Abstract: Introduction: Nutritional deficiency anaemia can lead to development of headache, fatigue, lethargy, apathy, exertional dyspnoea, palpitations and tinnitus and thereby decrease the quality of everyday life to a great extent. Such symptoms may pose a hindrance for students in their academic life and have a negative impact on their career. Aim:To determine prevalence of nutritional deficiency anaemia and its correlation with academic performance among medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The findings of the study showed that female students were more likely to be anemic compared to males. Previous studies reported similar findings that females are at more risk to develop anemia than males 6,7 . Females are prone to anemia because of menstruation.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The findings of the study showed that female students were more likely to be anemic compared to males. Previous studies reported similar findings that females are at more risk to develop anemia than males 6,7 . Females are prone to anemia because of menstruation.…”
Section: Discussionsupporting
confidence: 62%
“…Young people are particularly susceptible because of their rapid growth and associated high iron requirements 4 . Previous studies around the globe reported the prevalence of anemia among young adults 5,6 . A Bangladeshi study conducted in the Noakhali region reported 55.3% of adults university students to be anemic 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Blood loss in schoolchildren is caused by helminth infestations, which attack the proximal small intestine and suck blood from the intestinal submucous veins [ 23 , 24 ]. Children with anemia have a lower index of psychomotor development than healthy children [ 25 ]. Children with low Hb (anemia) have a low learning ability, and their school performance is also lower than that of normal children [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This in turn can reduce cognitive performance 22,23 . In the literature, various studies usually comparing anemic and non-anemic student groups have reported hemoglobin level has a positive or null effect on academic achievement 24 . In our study, the hemoglobin levels of the vast majority of the students were within the normal range and we did not detect a relationship between academic achievement and hemoglobin levels.…”
Section: Di̇scussi̇onmentioning
confidence: 99%